Removing Cerebrospinal Fluid Antibody Orders from the Test Menu Results in a Dramatic Decrease in Order Volume. (1st July 2017) - Beal, Stacy G; Tremblay, Elizabeth; Harris, Neil; Rand, Kenneth
Abstract: Background: Antibody tests for Borrelia burgdorferi (agent of Lyme disease), Toxoplasma gondii, and cytomegalovirus in cerebrospinal fluid (CSF) are rarely useful. One reason for misutilization of laboratory tests is simply the convenience offered by a computerized physician order entry (CPOE) system. Methods: The cytomegalovirus (CMV) antibodies-CSF, B. burgdorferi antibodies-CSF, and T. gondii antibodies-CSF orders were removed from the test menu. A provider could still order these tests using a miscellaneous order. We collected monthly volumes of test orders before and after the tests were removed from the CPOE. Results: Orders for CSF antibody testing for B. burgdorferi, T. gondii, and CMV decreased by 91%, 93%, and 98%, respectively ( P < 0.01), after they were removed from the CPOE test menu. This result correlates to a savings of 50053.44 per year. Additionally, we did not see a paradoxical increase in CMV PCR or T. gondii PCR orders after the intervention. Conclusions: Removal of test orders from the CPOE dramatically decreased test order volume, which led to substantial cost savings and availability of CSF for more useful tests. There was no compensatory increase in order volume for related tests, indicating that providers were not looking for alternate tests.